Analysis of Factors that Influencing Interest in Green Warehouse Adoption - Rifqi Fadilah; Muhammad Fariz Fauzan; Edi Abdurachman; Mohamad Zaini (Green Publisher, 2025)
The growth of the logistics sector in Indonesia has highlighted the importance of sustainable practices, including the adoption of green warehouses. This study investigates the factors influencing interest in green warehouse adoption, focusing on warehouse leader orientation, knowledge of green warehouses, and awareness of green warehouse regulations. Using a quantitative approach with a survey of 43 respondents from two institutions, the study employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) for analysis. The findings reveal that knowledge of green warehouses significantly and positively impacts the interest in adoption, while warehouse leader orientation and knowledge of regulations show no significant influence. The study underscores the importance of enhancing knowledge and awareness about green warehouses to promote their adoption and contribute to environmental sustainability in the logistics sector.